Підвищення якості електроенергії в експлуатаційних режимах судової системи охолодження - Міхайков, Сергій Сергійович; Муха, Микола Йосифович; Дранкова, Алла Олегівна (Національний технічний університет "Харківський політехнічний інститут", 2019)
У роботі приведений варіант підвищення якісних показників електроенергії суднової електромережі хімовозу в експлуатаційних режимах системи охолодження дизель-генераторів, що включає частотно-регульовані електроприводи насосів, шляхом застосування пасивних С-фільтрів. Оцінка таких показників якості електроенергії як коефіцієнтів гармонік і сумарних коефіцієнтів гармонік за напругою та струмом суднової електромережі при типових режимах роботи системи охолодження проведена на розробленій у середовищі MATLAB Simulink моделі «Суднова електромережа – система охолодження дизель-генераторів».

The paper presents a variant of improving the power quality parameters of the ship's power supply network of a chemical tanker inthe operating modes of the diesel generators cooling system, which fitted frequency-controlled electric drives of pumps, by using passive C-filters. The assessment of such power quality parameters as harmonic coefficients andtotal harmonic coefficients for the voltage and current of the ship's electrical network under typical operating conditions of the cooling system was carried out on the model “Ship's electrical network - diesel generator cooling system” developed in MATLAB Simulink. A generalized parameter of the qualityof the ship’s power grid, namely THD was obtained for all typical operation modes of a pump electric drives using a C-type filter. The paper gives recommendations on the use of C-type filters to improvethe quality of the chemical tanker autonomous power network for the diesel generators cooling system.
Improving the electric energy quality in operation modes of ship’scooling system
Keywords: показники якості електроенергії; частотний перетворювач; асинхронний двигун; контур охолодження дизель-генераторів; осцилограми напруги та струму; сумарний коефіцієнт гармонік (THD); electricity quality parameters; frequency converter; asynchronous motor; cooling system; oscillogram of voltage and current; total harmonic distortion (THD)